2011
DOI: 10.5194/acp-11-11951-2011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing regional scale predictions of aerosols, marine stratocumulus, and their interactions during VOCALS-REx using WRF-Chem

Abstract: Abstract. This study assesses the ability of the recent chemistry version (v3.3) of the Weather Research and Forecasting (WRF-Chem) model to simulate boundary layer structure, aerosols, stratocumulus clouds, and energy fluxes over the Southeast Pacific Ocean. Measurements from the VA-MOS Ocean-Cloud-Atmosphere-Land Study Regional Experiment (VOCALS-REx) and satellite retrievals (i.e., products from the MODerate resolution Imaging Spectroradiometer (MODIS), Clouds and Earth's Radiant Energy System (CERES), and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 60 publications
9
118
0
Order By: Relevance
“…Although there was a significant variability of the observed profiles (the largest for the horizontal velocity components within the boundary layer), the variability does not explain the systematic differences in the boundary layer height between the observations and simulations. Overall, significant underprediction of the height is consistent with previous limited-area simulations of cloud-topped marine boundary layer (e.g., Wyant et al, 2010;Abel et al, 2010;Yang et al, 2011;Wang et al, 2011). In our case, the underprediction results from a combination of two factors.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although there was a significant variability of the observed profiles (the largest for the horizontal velocity components within the boundary layer), the variability does not explain the systematic differences in the boundary layer height between the observations and simulations. Overall, significant underprediction of the height is consistent with previous limited-area simulations of cloud-topped marine boundary layer (e.g., Wyant et al, 2010;Abel et al, 2010;Yang et al, 2011;Wang et al, 2011). In our case, the underprediction results from a combination of two factors.…”
Section: Discussionsupporting
confidence: 79%
“…This is consistent with several previous investigations, such as Wyant et al (2010), Abel et al (2010), Yang et al (2011. The observed top of the approximately well-mixed boundary layer is between 1 and 1.5 km, but the model predicts the depth of between 0.5 and 1 km.…”
Section: Model Evaluation and Sensitivitysupporting
confidence: 81%
“…Similar results are found when we replace the Lin microphysics scheme by the two-moment Morrison scheme (Morrison et al, 2009). Previous model assessments also showed that the inclusion of aerosol indirect effects reduced cloud water content over the South Pacific Ocean and improved model comparison with aircraft observations (Yang et al, 2011). The relatively small precipitation, as well as small changes of precipitation due to aerosol feedbacks over the north of the domain, suggests that precipitation has a minor effect on near-surface aerosols in January 2013.…”
Section: Feedbacks On Meteorologysupporting
confidence: 69%
“…Aerosol particles can influence the earth's climate both directly by scattering and absorption of incoming solar radiation and terrestrial outgoing radiation, and indirectly by affecting cloud radiative properties through their role as cloud condensation nuclei (CCN) and ice nuclei (IN) (Twomey, 1974(Twomey, , 1991Charlson et al, 1992;Yu, 2000;Yu et al, 2000Yu et al, , 2001aYu et al, , b, 2003Yu and Zhang, 2011;Lohmann and Feichter, 2005;Menon et al, 2002Menon et al, , 2008IPCC, 2007;DeFelice et al, 1997;Chapman et al, 2009;Gustafson et al, 2007;Zhang et al, 2010aZhang et al, , b, 2012Tao et al, 2012;Hansen et al, 1997;Haywood and Boucher, 2000;Ramanathan et al, 2001;Rosenfeld et al, 2008;Saxena and Yu, 1998;Saxena et al, 1997;F. Yu et al, 2012a, b;Saide et al, 2012;Yang et al, 2011;Liu et al, 2011;McKeen et al, 2007;Yu et al, 2004Yu et al, , 2007bYu et al, , 2008. The aerosol indirect effect (AIE) can be split into the first, second, and glaciation aerosol indirect effects.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting cloud drop and ice number concentrations are added to the Morrison cloud microphysics scheme (Morrison et al, 2009(Morrison et al, , 2005, and this allows us to estimate aerosol effects on cloud and ice optical depth and microphysical process rates for indirect aerosol radiative forcing (including first, second and glaciation indirect aerosol forcing) by tying a two-moment treatment of cloud water (mass and number) and cloud ice (mass and number) to precipitation (the Morrison et al two-moment cloud microphysics scheme, Morrison et al, 2009Morrison et al, , 2005 and two radiation schemes (the Rapid Radiative Transfer Model for General Circulation Models (GCMs) (RRTMG), Iacono et al, 2008, andCAM, Collins et al, 2004) in the WRF model. The RRTMG and CAM radiation schemes are selected because these two schemes are used in many studies (Liu et al, 2007;Collins et al, 2004;Iacono et al, 2008;Yang et al, 2011;Saide et al, 2012). The comparison results of the WRF-CMAQ/CAM and WRF-CMAQ/RRTMG simulations can indicate the effects of radiation schemes on the model performance on air quality and cloud properties.…”
Section: Introductionmentioning
confidence: 99%